Predictors of postoperative recurrence in patients with non‐metastatic pT3a renal cell carcinoma. (3rd August 2021) - Ohsugi, Haruyuki; Ohe, Chisato; Yoshida, Takashi; Ikeda, Junichi; Sugi, Motohiko; Kinoshita, Hidefumi; Matsuda, Tadashi
Abstract : Objective: To analyze the effect of patterns of extrarenal tumor extension with other pathological factors on postoperative recurrence in patients with non‐metastatic pT3a renal cell carcinoma. Methods: We retrospectively reviewed 587 non‐metastatic renal cell carcinoma patients who underwent radical surgery between 2006 and 2017 at Kansai Medical University Hospital, Hirakata, Osaka, Japan. We extracted a subset of 114 patients with pT3a of predominant histological types: 93 with clear cell renal cell carcinoma (81.6%), 13 with unclassified renal cell carcinoma (11.4%), six with chromophobe renal cell carcinoma (5.3%) and two with papillary renal cell carcinoma. The primary end‐point was recurrence‐free survival. The Kaplan–Meier method and Cox proportional hazards model were used for statistical analysis. Results: Of the 114 patients with pT3a renal cell carcinoma, 42 patients (36.8%) experienced recurrence. Multivariate analysis showed that perinephric fat invasion (hazard ratio 2.36, P = 0.009), sarcomatoid or rhabdoid component (hazard ratio 2.88, P = 0.022) and necrosis (hazard ratio 2.34, P = 0.030) were independent factors for recurrence‐free survival. The high‐risk pT3a group, which had more than two independent predictors, had poor prognosis. Recurrence‐free survival of the high‐risk pT3a group and the pT3b or greater group were similar (median recurrence‐free survival 23.0 and 10.8 months, respectively). Conclusions: Perinephric fat invasion, sarcomatoid or rhabdoid component and necrosis are independent predictors of recurrence‐free survival in patients with pT3a‐predominant renal cell carcinoma. Patients with more than two of these predictors have poor oncological outcomes. These findings will aid in risk stratification for predicting recurrence and provide prognostic information for patient counseling.